Validation and Uncertainty Evaluation of an LC-DAD Method for Simultaneous Quantification of Benzoic Acid, Methylparaben, and N-Butylparaben in Soy Sauce - Aristiawan, Yosi; Ramadhaningtyas, Dillani Putri; Styarini, Dyah (Jurnal Riset Kimia, 2022)
Chemical food preservation is the common strategy used by human to preserve the natural properties and to increase the shelf life of food. Although preservatives are useful to keep the food fresh and to stop the bacterial growth, there are certain preservatives that are harmful if taken in more than the prescribed limits. Some of the typical used—benzoic acid, methylparaben, and n-butylparaben—were employed in this work with the aim of establishing a simultaneous liquid chromatography (LC) method for detecting each in soy sauce matrices. Liquid and C18 solid phase extraction were performed in this procedure prior to LC using Diode Array Detector analysis. In gradient elution of a format buffer (pH 4.4) and acidified acetonitrile, the target components were successfully separated. Calibration curve ranged from 0.61–140 mg/kg linearly while the limit of quantification for benzoic acid, methylparaben, and n-butylparaben were 0.41, 0.10, and 0.11 mg/kg, respectively. The intermediate precision and recovery were in the range between 0.15-1.89% and 100.5-103.3%, respectively. The expanded uncertainty (k=2) in sample measurement was estimated at 3.4-6.5%. The offered method was conformed to the validation acceptance criteria and can be applied as a routine method in the laboratory at ppm level.